Development of a portable electrocoagulation unit for on-site treatment of washing machine wastewater - Ayuque Rojas, José Carlos (2024)
his study evaluated the effectiveness of the electrocoagulation method in treating wastewater from two laundries in the Huancavelica district of Peru, focusing on reducing chemical oxygen demand (COD) and monitoring temperature and pH levels. Over two weeks, treatments were conducted with varying current intensities (15 and 30 Amp/m²) and durations (15 and 40 minutes), mixing speed + time (20 and 40 rpm) alongside a control with 0 Amp/m² and 0 minutes. The initial untreated samples showed high COD levels, highlighting significant organic pollution. The results demonstrated substantial COD reductions across all treatments, with the most effective reduction observed at 15 Amp/m² for 15 minutes, achieving COD levels of 366.50 mg/L in Laundry 1 and 348.50 mg/L in Laundry 2. This significant decrease complies with Supreme Decree No. 010-2019-VIVIENDA, which mandates COD levels below 1000 mg/L for non-domestic wastewater discharges. Temperature and pH variations were also analyzed, revealing that the electrocoagulation process increased the temperature moderately, with averages ranging from 15.15°C to 36.80°C in Laundry 1 and 15.65°C to 34.80°C in Laundry 2. The pH levels remained slightly alkaline, ranging from 8.47 to 10.55 in Laundry 1 and 9.47 to 10.62 in Laundry 2, indicating that the process maintains acceptable alkalinity. In conclusion, the electrocoagulation methodeffectively reducesCOD, maintainsmoderatetemperatureincreases, and slightlyalters pH levels, making it a viable option for treating industrial wastewater. These findings support the potential for electrocoagulation to enhance wastewater management practices, promoting environmental sustainability and regulatory compliance.